A STUDY ON SENIOR HIGH SCHOOL TEACHERS' ACCEPTANCE OF COMMUNITY-BASED LOCAL ENROLLMENT: Received: 6th January 2025, Revised: 14th February 2025, 26th February 2025, Accepted: 2nd April 2025, Date of Publication: 15th July 2025 - Lin Yi-Shan, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The community-based approach to high schools and vocational schools considers the convenience, necessity, geographical relevance, and suitability of students enrolling close to home. It aims to construct a reasonably defined "suitable learning community" by facilitating inter-school collaboration among high schools and vocational schools, as well as resource sharing with junior high schools, colleges, and social welfare organizations. This includes sharing curricula, teaching staff, and both software and hardware resources, thereby providing diverse and suitable learning opportunities for high school and vocational students. This study aims to explore high school teachers' acceptance of community-based local enrollment through the lenses of social change, industrial change, and career development, to understand how these changes influence career development and subsequently teachers' attitudes towards local enrollment implementation. The subjects of this study are high school teachers, and a convenience sampling method was used to collect data. A total of 230 questionnaires were distributed, with 203 valid responses returned. The data were analyzed using AMOS 20 for confirmatory factor analysis. The results indicate a highly significant positive correlation between industrial change and social change, a significant positive correlation between industrial change and career development, and a significant negative correlation between career development and attitudes towards local enrollment implementation.Community-Based Approach